Out‐of‐sequence thrusting in polycyclic thrust belts: An example from the Mesozoic Yanshan belt, North China Craton. Issue 9 (22nd September 2016) - Li, Chengming; Zhang, Changhou; Cope, Tim D.; Lin, Yi
Abstract: The EW trending Yanshan belt, an intraplate fold‐thrust belt located in the northern North China Craton that has experienced several episodes of deformation widely separated in time, is characterized by out‐of‐sequence thrusts. According to detailed mapping in the central Yanshan belt, five geometric and stratigraphic criteria used to aid in determining whether a thrust has an out‐of‐sequence geometry or not can be recognized. They are (1) unconformable relationships, (2) inclination of fault surfaces, (3) irregular changes in apparent offset along strike, (4) short fault length relative to apparent offset, and (5) in‐sequence geometry. With the help of these criteria, two generations of out‐of‐sequence thrusts that postdate the original in‐sequence thrusting in the central Yanshan belt are recognized. The ancestral southward verging fold‐and‐thrust belt that formed prior to 180 Ma was deformed and cut by two younger generations of faults that are probably more deeply rooted and are constrained to between 172–165 Ma and 152–135 Ma. A series of thrusts with opposite vergence formed during the last period, resulting in abundant abnormal field relationships such as younger‐on‐older thrust relations, fold truncation, and cutting down‐section. The nature and occurrence of faults in the Yanshan belt implies that superimposed deformation, a common feature in polycyclic orogenic belts, is a mechanism for the generation of out‐of‐sequence thrusting. This adds to mechanisms already described in the literature, such as maintaining constant critical taper at an orogenic scale, inhibition of the deformation front, and lateral changes in the nature of the décollement horizons. Key Points: The Yanshan belt is characterized by out‐of‐sequence thrusts that result from periods of shortening with significant erosion in between Five geometric criteria are recognized in order to aid in determining whether a thrust has an out‐of‐sequence geometry or not Two generations of out‐of‐sequence thrusts that postdate the original in‐sequence thrusting in the Yanshan belt are recognized